Peran Pendidikan Agama Islam Dalam Membentuk Karakter Jujur Pada Siswa - Nur Apriyani; Nursal Efendi (STAIN Bengkalis, 2023)
Character education is one of the rights that can be achieved in forming a whole human soul even though they are younger, but have faith and piety to God Almighty, have noble character, are capable, and are imaginative. The main purpose of learning PAI is the formation of personality in students which is reflected in their behavior and mindset in everyday life. This exploration is directed at SMA Negeri 14 Makassar. The technique used is quantitative methodology. The instrument used by the researcher is a survey test in this review. Class XII students of SMA Negeri 14 Makassar. Shows the ability level of the respondent in telling the truth 80.2. A positive reaction to the way they behave honestly is important for disciplining students in schools, families and the local environment. the respondent's ability to tell the truth is 80.2. A positive reaction to the way they behave honestly is important for disciplining students in schools, families and the local environment. An average score of 80.2 is obtained, this shows that the high value of trust claimed by each student. The percentage rates for each indicator will generally be rather high, despite the fact that at point 3, they really find it difficult to offer their point of view when they discover or track dishonesty and behavior.